2019
DOI: 10.1002/nbm.4195
|View full text |Cite
|
Sign up to set email alerts
|

Short‐ and long‐term reproducibility of BOLD signal change induced by breath‐holding at 1.5 and 3 T

Abstract: Cerebrovascular reactivity (CVR) can give insight into the cerebrovascular function. CVR can be estimated by measuring a blood-oxygen-level-dependent (BOLD) response combined with breath-holding (BH). The reproducibility of this technique has been addressed and existing studies have focused on short-term reproducibility using a 3 T magnetic resonance imaging (MRI) system. However, little is known about the long-term reproducibility of this procedure and the corresponding reproducibility using a 1.5 T MRI syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 47 publications
3
25
1
Order By: Relevance
“…Regarding CVR reliability, the whole-brain average reliability of SE-MPR was comparable to longterm reliability (days or weeks apart) found in previous studies of CVR induced by BH (Peng et al, 2019), by paced deep breathing (Sousa et al, 2014), or by gas challenges (Leung et al, 2016), and higher than that reported in other studies on BH induced CVR estimated with a non-lagged optimized P ET CO 2 hrf trace (Lipp et al, 2015) or with Fourier modelling (Pinto et al, 2016), and by gas challenges (Dengel et al, 2017;Evanoff et al, 2020). Consequently, the reliability of CVR estimates obtained with the optimal combination dataset and conservative ME-ICA modelling approaches were found higher than those previously reported in the literature.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Regarding CVR reliability, the whole-brain average reliability of SE-MPR was comparable to longterm reliability (days or weeks apart) found in previous studies of CVR induced by BH (Peng et al, 2019), by paced deep breathing (Sousa et al, 2014), or by gas challenges (Leung et al, 2016), and higher than that reported in other studies on BH induced CVR estimated with a non-lagged optimized P ET CO 2 hrf trace (Lipp et al, 2015) or with Fourier modelling (Pinto et al, 2016), and by gas challenges (Dengel et al, 2017;Evanoff et al, 2020). Consequently, the reliability of CVR estimates obtained with the optimal combination dataset and conservative ME-ICA modelling approaches were found higher than those previously reported in the literature.…”
Section: Discussionsupporting
confidence: 80%
“…Consequently, the reliability of CVR estimates obtained with the optimal combination dataset and conservative ME-ICA modelling approaches were found higher than those previously reported in the literature. However, all strategies produced a reliability that was lower than the short-term (within-session) reliability reported in BH induced CVR (Peng et al, 2019), resting state based CVR (P. Liu et al, 2017), and gas challenge induced CVR (Leung et al, 2016), although lower intersession reliability in gas challenges has also been reported (Dengel et al, 2017;Evanoff et al, 2020). Note that the reliability observed in this study seems to be globally higher and spatially less variable than that reported in previous studies (Lipp et al, 2015;Sousa et al, 2014).…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Summary MRI parameters for the BOLD gradient-echo echo-planar imaging (GE-EPI), pulsed continuous ASL (pCASL) and dual-echo ASL/BOLD GE-EPI techniques at 3 T are given in Table 2. Three studies (n = 18) found BOLD-derived CVR values were lower at lower magnetic field strengths (Driver et al, 2010;Triantafyllou et al, 2011;Peng et al, 2020), two of which (n = 9) reported a linear relationship between BOLD-derived CVR and the field strength (Driver et al, 2010;Triantafyllou et al, 2011). In one study (n = 16), ASL-derived CVR did not differ at different field strengths (Noth et al, 2006).…”
Section: Mri Techniquementioning
confidence: 94%
“…The CVR data were processed using the procedures described in the literature 25 . First, the BOLD data were corrected for head motion and temporally high‐pass filtered (1/128 Hz) via the SPM software.…”
Section: Methodsmentioning
confidence: 99%